(untitled) (International Seven Journal of Multidisciplinary, 2023)
Palliative care requires intervention in the care of patients in the initial, advanced or terminal stages of the disease, promoting comfort or control of signs and symptoms. According to this literature review, for patients in palliative care when there are signs of dyspnea leading to hypoxemia, the use of oxygen therapy may be indicated to correct the hypoxemic condition. The objective of this work is to understand the use of oxygen therapy in patients undergoing palliative care for advanced disease. The methodology used was a literature review research and the articles used were searched in the database: Pubmed, Electronic Library Online (SciELO), Latin American and Caribbean Health Sciences Literature (LILACS) and Google Scholar. According to the studies carried out, it was observed that the critically ill patient who is under palliative care, the improper use of oxygen supplementation can result in serious and harmful effects on health. Dyspnea is one of the most frequent symptoms presented by individuals with terminal illnesses or at the end of life. For this reason, the correct use of oxygen therapy in terminally ill patients can be a good reversal of dyspnea, providing better comfort and increasing the individual’s quality of life.